2015
DOI: 10.1103/physrevb.91.064510
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of superconductivity inLa1xSmxO0.5F0.5BiS

Abstract: The superconducting and normal-state properties of La1−xSmxO0.5F0.5BiS2 (0.1 x 0.9) have been studied via electrical resistivity, magnetic susceptibility, and specific heat measurements. By using suitable synthesis conditions, Sm exhibits considerable solubility into the CeOBiS2-type LaO0.5F0.5BiS2 lattice. In addition to a considerable enhancement of the superconducting volume fraction, it is found that the superconducting transition temperature Tc is dramatically enhanced with increasing Sm concentration to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
37
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Furthermore, several high-pressure studies revealed that superconducting properties are sensitive to changes in local crystal structures: the T c can be enhanced by optimal lattice contraction [20][21][22][23][24][25][26][27]. In addition, it was reported that the [31]. These experimental results suggest that the intrinsic (bulk and higher T c ) superconductivity could be induced by optimizing crystal structures in the BiS 2 -based family.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several high-pressure studies revealed that superconducting properties are sensitive to changes in local crystal structures: the T c can be enhanced by optimal lattice contraction [20][21][22][23][24][25][26][27]. In addition, it was reported that the [31]. These experimental results suggest that the intrinsic (bulk and higher T c ) superconductivity could be induced by optimizing crystal structures in the BiS 2 -based family.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally, these materials are quite similar to high- T c cuprates and iron pnictides and superconductivity is quite robust as evident from numerous studies on various site substitutions24303132. T c is enhanced in LnO 1- x F x BiS 2 by chemical pressure via partial or complete substitution of La by a smaller rare-earth (Ln = Ce, Pr, Nd, Sm and Yb)2333343536. YbO 0.5 F 0.5 BiS 2 has the highest T c  = 5.4 K among LnO 1- x F x BiS 2 and, interestingly, it undergoes an antiferromagnetic transition (T N  ~ 2.7 K) also23.…”
mentioning
confidence: 99%
“…However, the details of the BEC-BCS transition are not fully clear so far as well [2,20,21,26,31]. Pressure is a powerful tool for studying various properties of the cuprates [32][33][34][35][36][37][38] and it is widely used in experiments since the discovery of HTSCs [39] till present days [40]. Pressure noticeably affects T c and the resistance of HTSCs in the normal state.…”
Section: Introductionmentioning
confidence: 99%